Race, Gender, and Presentism in the Opera Studies Classroom - Esther M. Morgan-Ellis; Reba Wissner (Musica Docta)
In recent years, there has been much public debate about the staging of operas that might perpetuate racist and misogynist ideologies. Students who are trained to read such texts in the light of contemporary race and gender politics often find these historical theatrical works shocking. However, what seems regressive to students today sometimes served liberatory ends for audiences and artists in other times and places. When teachers help students interpret such works through a historical lens, they provide insight into the oppressive structures and forms of resistance that have always shaped the production and reception of musical theater. In this essay, we take Giacomo Puccini’s Madama Butterfly (1904) as a case study. We introduce primary and secondary sources that students can examine to better understand the politics of this opera at its premiere and throughout the 20th century. In doing so, we lay out a framework for teaching any piece of music that has meant different things to performers and audiences across time and place.